A modified longitudinal incision via transoral sublabial approach for removal of the nasal vestibular cyst: a clinical observation. Issue 10 (10th October 2020) - He, C; Li, W-L; Ye, C-G; Zhen, H-T
Abstract: Objective: The aim of this study was to investigate the clinical effect of the removal of nasal vestibular cysts through a modified longitudinal incision via a transoral sublabial approach. Method: In 28 cases, a nasal vestibular cyst was removed through a modified longitudinal incision via a transoral sublabial approach. A visual analogue scale score was used to evaluate the numbness of the nasal alar and upper lip. Post-operative complications were recorded. Medical photographs were used for assessment. Results: For all patients, incisions reached clinical primary healing one week after surgery. All patients were free of post-operative haematoma, infection, oronasal fistula and malformation. In the first week and the first month after surgery, numbness of the nasal alar and upper lip was recorded in few cases. The patients were followed up for 2–57 months without recurrence. Conclusion: Removal of nasal vestibular cysts via a transoral sublabial approach with a modified longitudinal incision is a minimally invasive and simple surgical method with few complications and a quick recovery.